Older women, intimate partner violence and mental health: a consideration of the particular issues for health and health care practice - McGarry, Julie; Ali, Parveen; Hinchliff, Sharron
Aims and objectives: The purpose of this meta-synthesis was to explore qualitative evidence in older women with a history of Intimate partner violence (IPV) and their accounts and experiences of mental health. Background Intimate partner violence significantly impacts the health and wellbeing of women who experience it. However, women who experience intimate partner violence do not form a homogenous group and the effect on older women has not been adequately distinguished. While there is a growing body of evidence to address this deficit, studies to date have tended to concentrate on older women’s experiences of intimate partner violence in totality and as such mental health issues have been subsumed as a part of the whole. Design: Meta ethnographic synthesis of qualitative evidence. Methods: A systematic search of PUBMED, Cumulative Index to Nursing and Allied Health Literature (CINAHL), COCHRANE , Medline and PsycInfo, Sci was completed. The search included articles published up until the end of December 2015. Results: The review identified that intimate partner violence exerts a significant impact on the mental health of older women. Iintimate partner violence for women in later life is inherently complex, especially where the boundaries of violence and vulnerability have been blurred historically both within the intimate partner violence discourse and through provision and practice. Conclusions: This paper adds to the developing knowledge and understanding of intimate partner violence for older women as a part of the growing body of evidence of the impact of IPV on the health and wellbeing of those who experience abuse more generally. When age and gender intersect with IPV, there are specific implications and health professionals and service providers need to be aware of these. Relevance to Clinical Practice: Nurses and health care professionals are professionally accountable for the effective management and support of women who have experienced abuse. It is therefore crucial that they are able to understand and identify the possible complexity of presentations of abuse and this includes older women.